2013
DOI: 10.1007/s12199-013-0335-9
|View full text |Cite
|
Sign up to set email alerts
|

Fatal child maltreatment associated with multiple births in Japan: nationwide data between July 2003 and March 2011

Abstract: Objectives The purpose of the present study is to clarify the impact of multiple births in fatal child maltreatment (child death due to maltreatment). Methods The national annual reports on fatal child maltreatment, which contain all cases from July 2003 to March 2011, published by the Ministry of Health, Labor and Welfare of Japan, were used as the initial sources of information. Parent-child murder-suicide cases were excluded from the analyses. Multiple births, teenage pregnancy and low-birthweight were rega… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
8
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 12 publications
2
8
1
Order By: Relevance
“…Further, analysis of the mediating effect of low birth weight was not possible because low-birth-weight infants were excluded. To the extent that our findings reflect infant death due to intentional injury, our results are consistent with previous studies which found that twins (or twin families) were at 2–20 times’ higher risk of abuse than singletons in the United States and in Japan (710).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Further, analysis of the mediating effect of low birth weight was not possible because low-birth-weight infants were excluded. To the extent that our findings reflect infant death due to intentional injury, our results are consistent with previous studies which found that twins (or twin families) were at 2–20 times’ higher risk of abuse than singletons in the United States and in Japan (710).…”
Section: Discussionsupporting
confidence: 92%
“…It is unknown whether twins and higher-order multiples are at greater risk of infant mortality from external causes. However, caring for multiple infants might lead to decreased parental attention per child (2); having multiples can increase parental anxiety, stress, and depression (3, 4), particularly during the first year of life (3, 5, 6); and multiples have been found to be at higher risk of child maltreatment than singletons (710).…”
mentioning
confidence: 99%
“…The annual reports by the Ministry of Health, Labor and Welfare of Japan also pointed out that having more than one child, including multiples, is one of the risk factors for child maltreatment, although no evidence has been shown by the Ministry. The present results and the higher prevalence of fatal child maltreatment observed in the same dataset (Ooki, 2013) support this point.…”
Section: Discussionsupporting
confidence: 86%
“…Multiple births are noted as one of the risk factors for child maltreatment, and having several siblings in the family is another risk factor . Although sibling age difference has not been reported as a risk factor, a 1 year difference between siblings was noted in three cases in the present study.…”
Section: Discussioncontrasting
confidence: 55%